The responsibility to provide in Southeast Asia : towards an ethical explanation - Tan, See Seng, 1965- (Bristol University Press, 2019)
Despite a long-held ASEAN principle of non-intervention, this theoretically rich book argues that there is an embryonic ethic of regional responsibility emerging among the countries of southeast Asia which reflects an evolution of attitudes about state sovereignty.
Keywords: Sovereignty.; Southeast Asia -- Foreign relations.; International cooperation.; International Cooperation; Souveraineté.; Asie du Sud-Est -- Relations extérieures.; Coopération internationale.; sovereignty.; POLITICAL SCIENCE -- International Relations -- General.; Diplomatic relations; International cooperation; Sovereignty; Southeast Asia